2017
DOI: 10.5194/aab-60-161-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the <i>IGF-I</i> gene polymorphism on growth, body size, carcass and meat quality traits in Coloured Polish Merino sheep

Abstract: Abstract. Insulin-like growth factor I, encoded by the IGF-I gene, plays a role in cell growth and differentiation, embryogenesis, metabolism regulation, skeletal growth, and protein synthesis. The aims of this study were to investigate the polymorphism in the 5 flanking region of the IGF-I gene and evaluate associations between the single-nucleotide polymorphism (SNP) in this gene and growth, body size, carcass and meat quality traits in Coloured Polish Merino sheep. In total 78 live and post mortem traits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
3
11
1
1
Order By: Relevance
“…The IGF1 SNP genotyped in Sarda sheep (rs159876390) was associated with protein and casein contents (P < 0.05). This result was not described in previous reports, where attention was more focused on growth-related traits (Grochowska et al, 2017) and reproduction traits (He et al, 2012). Crisà et al (2010) Figure 2.…”
Section: Discussioncontrasting
confidence: 93%
“…The IGF1 SNP genotyped in Sarda sheep (rs159876390) was associated with protein and casein contents (P < 0.05). This result was not described in previous reports, where attention was more focused on growth-related traits (Grochowska et al, 2017) and reproduction traits (He et al, 2012). Crisà et al (2010) Figure 2.…”
Section: Discussioncontrasting
confidence: 93%
“…In total, 106 ram lambs at mean age 105 days (SD 4.2, range 92-119 days) were chosen for slaughter during the three years of the study. Slaughtering, carcass cutting, and leg dissection were done in the abattoir of the NRIAP Experimental Station Kołuda Wielka as described previously by Grochowska et al [23,24] according to the methodologies of Nawara et al [25] and Krupiński et al [26]. In brief, the slaughtering of ram lambs took place in batches, three or four times a year from March to April.…”
Section: Carcass Traitsmentioning
confidence: 99%
“…The result of this study is different than results reported by Su et al (2014) who mentioned that IGF-I expression in Hu sheep increased from 2 days of birth and then continuously decreased until 3 months of age; thereafter, IGF-I expression gradually increased and reached the peak at 6 months of age, the expression of IGF-I in sheep that were 6 months of age was significant (P<0.01) and greater than at 1, 2, 3, and 4 months of age. The IGF1 gene plays an important purpose in the growth of multiple tissues, including mammalian muscle, somatic growth, and tissue repair (Nazari et al, 2016, Grochowska et al, 2017Rotwein, 2017). IGF-1 gene is considered to be a candidate gene for predicting growth and meat quality traits in sheep genetic improvement schemes.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Even though the IGF-I gene plays a role in the growth of an organism, it could also be directly or indirectly associated with other traits, i.e. carcass and meat quality traits (Grochowska et al, 2017).…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation